Pre-Service Teacher Perception Related to the Benefits of Micro-Teaching Course To Their Teaching Apprenticeship Program - Noha; Ida Yulianawati; Indra Yoga Prawiro (National Conference on Language, Education, and Technology Proceeding, 2023)
This study aims to explore pre-service teachers’ perceptions related to the benefits of micro-teaching class they have attended to their teaching apprenticeship. By using qualitative research, the data were obtained from questionnaire and interview. Participants this study are 8 pre-service teachers from 8th semester of Wiralodra University. The findings showed that pre-service teacher perception on micro teaching to their teaching apprenticeship program is micro teaching very benefited to pre-service teacher on their apprenticeship. The benefits are micro teaching supports in practicing, boost the confident, helps to make a systematic lesson plan, enables to gain instant feedback, and provides master a number of skill. This research suggests the investigation of the impact of microteaching to the pedagogical implementation of the pre-service teacher in the apprenticeship program.